2020
DOI: 10.21776/ub.jkb.2020.031.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Tulsi (Ocimum sanctum) Leaf Ethanol Extract Reduces Inflammatory Cell Infiltration in Aspirin-Induced Gastritis Rats

Abstract: <p class="ISIABSTRAKINGGRIS">Gastritis is an inflammation of the gastric mucosa. Tulsi leaf extract has phenol, flavonoid and saponin compounds which are potential as antioxidant and increase defensive factors in the gastric. The purpose of this research was to find out the effect of tulsi (Ocimum sanctum) leaf extract in polymorphonuclear (PMN) inflammatory cell infiltration in gastric of aspirin-induced gastritis rat model. This study was laboratory experimental research using post-test only control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…8 Another research by Festi et al showed that administration of Ocimum sanctum leaf extract at a dose of 400 mg/kg BW can reduce the degree of inflammation by decreasing the average number of infiltrating PMD inflammatory cells in the stomach of gastritis rat models. 16 This strengthens the theory that a dose of 400 mg/kg BW is an effective dose in inhibiting steatosis because it also inhibits inflammatory pathways.…”
Section: Administration Of Basil Leaves Extract On the Number Of Stea...supporting
confidence: 66%
“…8 Another research by Festi et al showed that administration of Ocimum sanctum leaf extract at a dose of 400 mg/kg BW can reduce the degree of inflammation by decreasing the average number of infiltrating PMD inflammatory cells in the stomach of gastritis rat models. 16 This strengthens the theory that a dose of 400 mg/kg BW is an effective dose in inhibiting steatosis because it also inhibits inflammatory pathways.…”
Section: Administration Of Basil Leaves Extract On the Number Of Stea...supporting
confidence: 66%
“…Basil leaves, herbs from the Ocimum family have been proposed to possess antihyperglycemic properties in multiple studies [16], [17], [20], [29], [30], [31]. This study found significant blood glucose -lowering effect and endothelial protection of basil leaves.…”
Section: Discussionmentioning
confidence: 66%
“…Insulin-secretory effect of the Ocimum family was elucidated by Hannan et al, as the extract enhances effects of insulin secretion from the pancreas, isolated islets, and modulation of intracellular calcium [30]. Basil leaves also shown to possess insulinotropic effect through the enhancement of physiological pathways on pancreatic beta-cells [20]. Thus, increasing plasma insulin and decreasing BGL in rats with type 2 diabetes [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 The extract also enhances physiological pathways on pancreatic β-cells, indicating its insulinotropic potency. 22 Ezeani et al showed that basil leaf extract could inhibit α-amylase and α-glucosidase, which suppress carbohydrate metabolism and the consequent glucose release from the small intestine lumen, leading to its postprandial anti-hyperglycaemic effect. 12 Basil leaf extract exhibited safety and similar efficacy when administered both acutely and chronically.…”
Section: Resultsmentioning
confidence: 99%